Influence surfaces by boundary element/least square methods coupling. (April 2016) - Almeida, Valério; Oliveira Neto, Luttgardes
Abstract This work presents a new application for calculating the influence surfaces of transverse displacements, directional derivatives and bending moments for generic bridge decks. A plate bending boundary element method formulation is coupled with the application of a continuous field surface derived by the least square procedure. This original BE formulation permits calculating influence surfaces of plates with polygonal, curved or circular geometry, and several transverse load conditions. The proposal allows future analysis of building floors and single and continuous bridge trusses connected to longitudinal and transversal girders. Numerical examples are presented to demonstrate the potential of the present formulation and the results are compared with analytical values and with usual vehicular loads.